The journey of metformin from glycaemic control to mTOR inhibition and the suppression of tumour growth. Issue 1 (8th November 2018) - Amin, Sam; Lux, Andrew; O'Callaghan, Finbar
Abstract : Our knowledge of the effect of metformin on human health is increasing. In addition to its ability to improve the control of hyperglycaemia, metformin has been shown to reduce the burden o, f ageing via effects on damaged DNA and the process of apoptosis. Studies have shown that metformin may reduce the risk of cardiovascular disease through influences on body weight, blood pressure, cholesterol levels and the progression of atherosclerosis. Studies also suggest that metformin may be beneficial for neuro‐psychiatric disorders, cognitive impairment and in reducing the risk of dementia, erectile dysfunction and Duchenne muscular dystrophy. In vivo and in vitro studies have shown that metformin has anti‐cancer properties, and population studies have suggested that metformin may reduce the risk of cancer or improve cancer prognosis. It is thought that it exerts its anti‐cancer effect through the inhibition of the mammalian target of rapamycin (mTOR) signalling pathway. Because of its effect on the mTOR pathway, there may be a role for metformin in slowing or reversing growth of life‐threatening hamartomas in tuberous sclerosis complex.